Microbial phosphotriesterase: structure, function, and biotechnological applications - Latip, Wahhida; Knight, Victor Feizal; Abdul Halim, Norhana; Ong, Keat Khim; Mohd Kasim, Noor Azilah; Wan Yunus, Wan Md. Zin; Mohd Noor, Siti Aminah; Mohamad Ali, Mohd Shukuri (MDPI, 2019)
The role of phosphotriesterase as an enzyme which is able to hydrolyze organophosphate compounds cannot be disputed. Contamination by organophosphate (OP) compounds in the environment is alarming, and even more worrying is the toxicity of this compound, which affects the nervous system. Thus, it is important to find a safer way to detoxify, detect and recuperate from the toxicity effects of this compound. Phosphotriesterases (PTEs) are mostly isolated from soil bacteria and are classified as metalloenzymes or metal-dependent enzymes that contain bimetals at the active site. There are three separate pockets to accommodate the substrate into the active site of each PTE. This enzyme generally shows a high catalytic activity towards phosphotriesters. These microbial enzymes are robust and easy to manipulate. Currently, PTEs are widely studied for the detection, detoxification, and enzyme therapies for OP compound poisoning incidents. The discovery and understanding of PTEs would pave ways for greener approaches in biotechnological applications and to solve environmental issues relating to OP contamination.